Metformin regulates bone marrow stromal cells to accelerate bone healing in diabetic mice - Yuqi Guo; Jianlu Wei; Chuanju Liu; Xin Li; Wenbo Yan (eLife, 2023)
Diabetes mellitus is a group of chronic diseases characterized by high blood glucose levels. Diabetic patients have a higher risk of sustaining osteoporotic fractures than non-diabetic people. The fracture healing is usually impaired in diabetics, and our understanding of the detrimental effects of hyperglycemia on fracture healing is still inadequate. Metformin is the first-line medicine for type 2 diabetes (T2D). However, its effects on bone in T2D patients remain to be studied. To assess the impacts of metformin on fracture healing, we compared the healing process of closed-wound fixed fracture, non-fixed radial fracture, and femoral drill-hole injury models in the T2D mice with and without metformin treatment. Our results demonstrated that metformin rescued the delayed bone healing and remolding in the T2D mice in all injury models. In vitro analysis indicated that compromised proliferation, osteogenesis, chondrogenesis of the bone marrow stromal cells (BMSCs) derived from the T2D mice were rescued by metformin treatment when compared to WT controls. Furthermore, metformin could effectively rescue the impaired detrimental lineage commitment of BMSCs isolated from the T2D mice in vivo as assessed by subcutaneous ossicle formation of the BMSC implants in recipient T2D mice. Moreover, the Safranin O staining of cartilage formation in the endochondral ossification under hyperglycemic condition significantly increased at day 14 post-fracture in the T2D mice receiving metformin treatment. The chondrocyte transcript factors SOX9 and PGC1α, important to maintain chondrocyte homeostasis, were both significantly upregulated in callus tissue isolated at the fracture site of metformin-treated MKR mice on day 12 post-fracture. Metformin also rescued the chondrocyte disc formation of BMSCs isolated from the T2D mice. Taken together, our study demonstrated that metformin facilitated bone healing, more specifically bone formation and chondrogenesis in T2D mouse models.